(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In the context of transformational shifts in the global economic space and the destructive impact of political and economic imbalances, the issue of ensuring the financial security of business entities through the prism of a value-oriented approach becomes particularly relevant. Financial security as a category of macro- and microeconomic stability integrates a complex set of factors, among which value determinants play a system-forming role. However, in the context of volatility of the external environment, asymmetry of information flows, erosion of investment capital and endogenous instability of management decisions, traditional approaches to identifying and assessing value factors lose their relevance. Purpose. The purpose of the study is to substantiate the theoretical and methodological principles and applied approaches to identifying, assessing and optimizing cost factors that affect the level of financial security of business entities, taking into account modern risks and challenges of the economic environment. Methods. In the context of studying the cost factors of ensuring the financial security of business entities, the methodological base is a key determinant of the reliability of analytical conclusions and the relevance of applied recommendations. Given the complex nature of the subject area, which involves an interdisciplinary combination of financial analysis, managerial economics and strategic management, the work used a set of general scientific and specialized methods that ensure a high level of theoretical and methodological verification of the results obtained, namely - the method of content analysis, the method of induction and deduction, the abstract method, the method of logical generalization. Results. The article examines the cost factors of financial security and the principles of their functioning. It is found that the synergistic interaction between the structural and dynamic characteristics of costs and the strategic risk management system ensures the generation of stable financial contours. It is proven that the variability of cost parameters is subject to indicative validation due to the multifactorial influence of external and internal determinants. Critical points of financial sensitivity associated with exceeding the optimal level of cost margin are identified. The need to structure the concept of financial security in the coordinates of a value-oriented management model is proven. Conclusions. In modern conditions, cost factors act as key transmission components of financial security, determining the level of adaptive resistance of a business entity to multi-vector destructive impulses. Their systemic integration into the management circuit ensures the formation of flexible mechanisms of internal financial compensation and neutralization of critical deviations in the cost environment.